Epistolary Poetry in Byzantium and Beyond An Anthology with Critical Essays (Taylor & Francis, 2021)
Literary Criticism, Mediterranean Literature, Poetry, Greek literature
English
Keywords: Literature: history and criticism; Literary Criticism, Mediterranean Literature, Poetry, Greek literature